VML (Voice Mail Learning): A New Normal Learning Platform in Aiding Learning Difficulty in Science 10-Biology - Mark Anthony Tangan (MultiTech Publisher, 2023)
Abstract Although widely used instant messaging apps like Facebook and Messenger were not designed as teaching tools, they have evolved into venues for peer review and aid to learning. This study aimed to utilize messenger as a friendly and widely used social media app as tool in aiding learning difficulty particularly in Biology through Voice Mail Learning. A One group Pretest and Posttest design was used in gathering the test scores of the 50 respondents during the pilot implementation of face-to-face classes SY 2021-2022. The SPSS was utilized to treat the gathered data. The study revealed that the posttest results were significantly higher that the pretest at 73.31 percent as compared to 29.46 percent. Thus, a post posttest was conducted 2 months after the posttest was administered to ensure that the platform is still in effect. The results exuded 84.74 percent efficiency. The utilization of digital tools was indispensable in this era. This study recommends the widely use of Voice Mail Learning not only as aid in teaching but also an aid in learning difficulty in other major subjects.